CRITÈRES EFFICACES ET MÉTHODOLOGIE POUR L'APPRENTISSAGE D'UNE LANGUE ETRANGÈRE («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article presents an overview of effective criteria and methods of learning foreign languages. The key criteria for successful learning and the principles of effective language immersion are discussed. Contextual learning, with the active participation of students and their ongoing practice, is of particular importance.
Keywords: Foreign language, effectiveness criteria, communicative approach, contextual learning.